The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0085-56262010000400019
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional ecology of blowflies (Diptera, Calliphoridae): estimates of critical larval weight for pupation on two different

Abstract: ABSTRACT. Nutritional ecology of blowflies (Diptera, Calliphoridae): estimates of critical larval weight for pupation on two different diets. Under natural environmental conditions, blowflies utilize discrete and ephemeral feeding resources such as decaying carcasses. Competition for food on such feeding substrates is usually very severe, and only the individuals that are capable of attaining the critical larval weight for pupation will be able to survive. This critical weight is hitherto unknown for several b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…According to this hypothesis, larvae bred on caustic soda produced smaller flies and more females than larvae bred in control conditions (Figs and , Table ). The adult size also strongly correlated with larval weight . Thus, the small size of the adults observed in the presence of caustic soda or citronella repellent and the high pupal mortality may be due to food‐deprived larvae .…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…According to this hypothesis, larvae bred on caustic soda produced smaller flies and more females than larvae bred in control conditions (Figs and , Table ). The adult size also strongly correlated with larval weight . Thus, the small size of the adults observed in the presence of caustic soda or citronella repellent and the high pupal mortality may be due to food‐deprived larvae .…”
Section: Discussionmentioning
confidence: 93%
“…Former studies reported that larvae need to reach a critical mass to pupate and successfully develop into adult flies . Ribeiro and Von Zuben also noted that the critical weights of larvae needed to produce viable pupae were lower for females than for males. The authors hypothesized that this difference is an evolutionary strategy that favored the establishment of future generations.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies on Calliphoridae suggest that a critical weight is required to enter pupation (Ribeiro & von Zuben, ; Muntzer et al ., ). However, the high survival rate of postfeeding larvae observed during the present study indicates that most individuals, even those with the fastest development (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Arthropods in most urban systems are controlled through resource-based competition or bottom-up forces [110]. While the availability of domestic food waste and animal feces increases the availability of food, the poor nutritional value of such substances is often unable to sustain developing larvae, reducing survival, fecundity, and the size of adults [111,112]. While such an observation is anecdotal at this stage, L. sericata adult specimens in the current survey were noticeably smaller than specimens examined from other regions.…”
Section: Discussionmentioning
confidence: 99%